Estimation of antiflatter properties of control actuators of various kinematic arrangement - Зайончковський, Г. Й. (Proceedings of National Aviation University (archive), 2000)
Shown are potential antiflatter properties of actuators with reversible kinematics based on the analysis of the properties of dynamic stiffness of control hydromechanical actuators used in control system of aircraft. Proposed are the recommendations concerning prevention of aircraft control surfaces flatter oscillations when booster control system is used